Synthetic analogues of the active site of [NiFe] hydrogenase - Skelton, Gemma (2017)
This thesis describes the synthesis of new [Ni]- and [NiFe]-containing complexes as analogues of the active site of the [NiFe] hydrogenases and which have the potential as catalysis for the electro- or photochemical production of H2. The research described in the thesis focuses on two key aspects: (i) the modulation of the potential at which proton reduction may occur through the nature of the ligand about the metal centres and (ii) the incorporation of photosensitiser units into [Ni]- and [NiFe]-containing complexes. Chapter 1 provides an introduction to the [FeFe] and [NiFe] hydrogenases and provides the context for the research carried out in this thesis. Relevant coordination chemistry is surveyed with a focus on mononuclear and heteronuclear coordination compounds containing Ni-centres in S-rich coordination environments. The electro- and photocatalytic properties of some of the centres are discussed. Chapter 2 describes the attempted synthesis and characterisation of the novel [Ni(p-qdtR1,R2)] (R1 = R2 = Me ; R1= H and R = tBu) and [Ni(p-q6,7dtR1,R2)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu) complexes. The complexes contain quinoxaline units that (i) may shift the reduction potentials to more positive for each complex and (ii) contain N atoms that may serve as protonation sites that may facilitate the reduction of protons. [Ni(p-q6,7dtR1,R2)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu) undergo an electrochemically reversible reduction process at ca. -1.47 V vs Fc+/Fc to generate the EPR-active [Ni(p-q6,7dtR1,R2)]- anions. The spin Hamiltonian parameters derived from simulations of the EPR spectra are consistent with a SOMO that is principally metal-centred. Density functional calculations provide a framework for the interpretation of the spectroscopic properties of [Ni(p-q6,7dtR1,R2)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu) and suggest that the redox-active LUMO is delocalised over the NiS4 centre. Cyclic voltammetric measurements of [Ni(p-q6,7dtR1,R2)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu) in acidic solutions show that these complexes are potential electrocatalysts for the reduction of H+ and operate at ca. -1.7 V vs Fc+/Fc at a comparable potential to [Ni(LA)]. Comparisons of the cathodic currents produced by [Ni(p-q6,7dtR1,R2)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu), [Ni(LA)] and [Ni(LA)Fe2(CO)6] suggest that the catalytic activities of [Ni(p-q6,7dtR1,R2)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu) and [Ni(LA)] are comparable and higher than that for the benchmark [Ni(LA)Fe2(CO)6] compound. Chapter 3 describes the syntheses and characterisations of [Ni(qdtR1,R2)(dppe)] (R1 = R2 = Me; R1 =H and R2 = tBu) and [Ni(q6,7dtR1,R2)(dppe)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu) complexes [Ni(qdtR1,R2)(dppe)] (R1 = R2 = Me; R1 = H and R2 = tBu) and [Ni(q6,7dtR1,R2)(dppe)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu) undergo an electrochemically reversible reduction process at ca. -1.79 and ca. -1.86 V vs Fc+/Fc, respectively, to generate the EPR-active [Ni(qdtR1,R2)(dppe)]- and [Ni(q6,7dtR1,R2)(dppe)]- anions. The EPR spectra are consistent with DFT calculations that reveal SOMOs that involve contributions from Ni 3dxy and S/P-σ combinations. Cyclic voltammetric studies show that [Ni(qdtR1,R2)(dppe)] (R1 = R2 = Me; R1 = H and R2 = tBu) and [Ni(q6,7dtR1,R2)(dppe)] (R1 = R2 = Me, Et and Ph; R1 = H and R tBu) are electrocatalysts that function at ca. -1.8 V vs Fc+/Fc, and comparisons of the cathodic currents produced by [Ni(qdtR1,R2)(dppe)] (R1 = R2 = Me; R1 = H and R2 = tBu), [Ni(q6,7dtR1,R2)(dppe)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu), [Ni(p-q6,7dtEt,Et)] and [Ni(LA)Fe2(CO)6] suggested that the catalytic activities of [Ni(qdtR1,R2)(dppe)] (R1 = R2 = Me; R1 = H and R2 = tBu) and [Ni(q6,7dtR1,R2)(dppe)] (R1 = R2 = Me, Et and Ph; R1 = H and R = tBu) are comparable to [Ni(LA)Fe2(CO)6] and lower than that for [Ni(p-q6,7dtEt,Et)]. Chapter 4 discusses the reactions of the NiII precursor complexes [Ni(p-qdtR1,R2)] [Ni(p-q6,7dtR1,R2)], [Ni(qdtR1,R2)(dppe)] and [Ni(q6,7dtR1,R2)(dppe)] described in Chapters 2 and 3 with [Fe]-containing fragments to isolate [NiFe] compounds as analogues of the active sites of the [NiFe] hydrogenases. The syntheses of [Ni(q6,7dtR1,R2)2Fe2(CO)6] and [Ni(q6,7dtR1,R2)2FeCp(CO)2](BF4) were confirmed by FTIR spectroscopy and mass spectrometry and [Ni(q6,7dtMe,Me)2Fe2(CO)6] was characterised by X-ray crystallography. In addition, [Ni(q6,7dtEt,Et)2Fe2(CO)6] and [Ni(q6,7dtH,tBu)2Fe2(CO)6] undergo an electrochemically reversible reduction process at ca.-1.22 V vs Fc+/Fc. FTIR spectroscopy confirms the successful synthesis of [Ni(q6,7dtR1,R2)(dppe)FeCp(CO)2](BF4) and [Ni(q6,7dtEt,Et)(dppe)FeCp(CO)2](BF4) and [Ni(q6,7dtH,tBu)(dppe)FeCp(CO)2](BF4) were characterised by X-ray crystallography. Chapter 5 describes research towards the incorporation of photosensitising units into [Ni]- and [NiFe]-containing complexes. A novel dithiol substituted dppz complex, [Ni(dppz(S)2)(dppe)], was characterised by X-ray crystallography and represents the first example of a NiII centre bound to S-donors from a dppz ligand. Additional reactions between this unit and [ReCl(CO)3] fragments, and between [ReCl(CO)3(dppz(S)2)] and NiII-precursors are described, together with attempts to synthesise a NiS4 complex containing two dppz units. Chapter 6 draws together the main conclusions of the thesis and suggests areas for future work.